Border-zone cardiomyocytes and macrophages regulate extracellular matrix remodeling to promote cardiomyocyte protrusion during cardiac regeneration - Constanty, Florian; Wu, Bailin; Wei, Ke-Hsuan; Lin, I.-Ting; Dallmann, Julia; Guenther, Stefan; Lautenschlaeger, Till; Priya, Rashmi; Lai, Shih-Lei; Stainier, Didier; Beisaw, Arica (Nature Communications, 2025)
Despite numerous advances in our understanding of zebrafish cardiac regeneration, an aspect that remains less studied is how regenerating cardiomyocytes invade and replace the collagen-containing injured tissue. Here, we provide an in-depth analysis of the process of cardiomyocyte invasion. We observe close interactions between protruding border-zone cardiomyocytes and macrophages, and show that macrophages are essential for extracellular matrix remodeling at the wound border zone and cardiomyocyte protrusion into the injured area. Single-cell RNA-sequencing reveals the expression of mmp14b, encoding a membrane-anchored matrix metalloproteinase, in several cell types at the border zone. Genetic mmp14b mutation leads to decreased macrophage recruitment, collagen degradation, and subsequent cardiomyocyte protrusion into injured tissue. Furthermore, cardiomyocyte-specific overexpression of mmp14b is sufficient to enhance cardiomyocyte invasion into the injured tissue and along the apical surface of the wound. Altogether, our data provide important insights into the mechanisms underlying cardiomyocyte invasion of the collagen-containing injured tissue during cardiac regeneration.